Kajian Dampak Sanitasi Total Berbasis Masyarakat Terhadap Akses Sanitasi di Kabupaten Wonogiri - Ichwanudin, Ichwanudin (Jurnal Kesehatan Lingkungan Indonesia, 2016)
Title: The Impact  Study of Community Based Total Sanitation  to Sanitation Access in District of Wonogiri.Background: Enhancement number of achievement sanitation access in District of Wonogiri decline every years in last three years. Enhancement sanitation access in 2012 is 4,1%, 2013 is 3,1% and 2014 is 1,6%. While improved sanitation facility growth in 2013 and 2014 only 1,3%.Methode: This research aimed to description various enabling factors CBTS to sanitation access enhancement in District of Wonogiri. This research was an analytic with cross sectional approach. The samples were 7 peoples member of AMPL organization, 25 peoples sub-district government agency and 73 village government agency. The data was analyzed by Mann-Whitney test, Kruskall Wallis test and Correlation Pearson. Results: Based on researh, AMPL manage organization performance is good. Sub-district which as CBTS manage organization reach 68% while village only 25%. Sanitation access poliy realitation in sub-district is 24% and village 25%. Sub-district government rating that Public Health Care Headman with big contribute in sanitation access enhancement is 48% and village government is 29%. BOK funding allocation enhancement average is 44%. Only one sub-district has organized capacity building.Conclusion: Analysis results refer to CBTS manage organization performance, Policy,  Capacity Building in sub-district and village, Public Health Care Headman policy, not different contribute for sanitation access in District of Wonogiri. While BOK funding allocation enhancement not influence sub-district sanitation access enhancement in District of Wonogiri.